Polymer-coated magnetic nanoparticles and modified polymer nanofibers for the efficient capture of Mycobacterium tuberculosis (Mtb) - Smit, Marica (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.